Heart rate variability of high producing cows in a parallel milking system - Kovács, Levente; Kézér, Luca; Jurkovich, Viktor; Nagy, Krisztina; Szenci, Ottó; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2025)
Stress response of milking cows (n = 36) during the evening milking procedure in a parallel milking system were evaluated in this study. Changes in heart rate (HR) and heart rate variability (HRV) during early afternoon (reference period) were compared to those measured during the different parts of the evening milking: 1. before the evening milking, in the milking parlor, waiting for being milked, 2. during milking, 3. in the milking parlor after being let off from the milking stall. HR was significantly higher during the entire evening milking procedure compare to the reference period (P < 0.05). HRV during milking did not differ significantly from the reference period, but lower HRV was found during waiting in the milking stall after milking (HFnorm = 33.7 ± 23.5) than during the reference period (HFnorm = 52.8 ± 13.6) also than during evening resting (P < 0.001) but there were no significant differences between milking and resting in HRV. The results suggest that the evening milking was not really stressful for these animals. The greatest stress level was caused by the anticipation for getting out from the milking parlour. More research is needed for assess the stress-coping ability during milking.